PELATIHAN PEMBUATAN ECO ENZYME DARI LIMBAH PERTANIAN DAN RUMAH TANGGA SEBAGAI PUPUK ORGANIK BAGI MASYARAKAT DI DESA TUBLOPO, KABUPATEN TIMOR TENGAH UTARA - Tea, Marselina Theresia Djue; Pramita, Dira Asri; Kadju, Fransiskus Yulius Dhewa (Universitas Nusa Cendana, 2022)
This community service activity was implemented at the Sehati Banopo Farmers Group, Tublopo Village, South Bikomi District, North Central Timor Regency, East Nusa Tenggara Province. The purpose of this service is to: (1) increase the knowledge and skills of rural communities to produce Eco Enzyme products from agricultural and household waste, and (2) provide understanding to the community regarding the use of Eco Enzyme as an organic fertilizer capable of preserving land. The implementation of the activity uses a training method that begins with initial observations and discussions related to the technical implementation of activities, coordination of the service team with village communities, and socialization and training activities for making Eco Enzyme. The next evaluation stage is carried out after the product has been fermented for three months, starting with the harvesting stage of Eco Enzyme and followed by the process of using it as organic fertilizer on agricultural land. The service activities went smoothly, which was marked by the appreciation and enthusiasm of the Tublopo Village community while carrying out the activities of making Eco Enzyme. Keywords: eco enzyme, waste, organic fertilizer